On low-velocity impact behaviour of composite laminates: Damage investigation and influence of matrix and temperature. (1st February 2022) - Lopresto, V.; Langella, A.; Pagliarulo, V.; Papa, I.
Abstract: The present manuscript aims to provide an overview of the phenomenon of the low-velocity impact behaviour of composite materials at room and in extreme temperature conditions, by comparing the results obtained on different fibre-matrix combinations and giving a comprehensive review of the impact behaviour and evolution of damage of marine and aerospace composites. The latter was chosen to reduce the environmental impact of plastic wastes. Experimental impact tests up to complete penetration and at different increasing impact energy levels, were carried out by a modular falling weight tower. The ability of different Non Destructive Techniques NDT in detecting and evaluating barely-visible and invisible impact damage on composite laminates was tested. The aspect related to the damage is, in fact, crucial for these materials because of their inhomogeneity and anisotropy. The conventional and largely used UltraSound technique, US, was adopted to investigate the delamination caused by low-velocity impact loads. The results were compared with Electronic Speckle Pattern Interferometry, ESPI, as well as with theoretical and semiempirical formulations for the delamination prediction.